The contribution of tidal currents in the sedimentation of the Strait of Avlida, Southern Evoikos Gulf (Greece) - ΠΟΥΛΟΣ Σ. E.; ΔΡΑΚΟΠΟΥΛΟΣ Π. Γ.; ΛΕΟΝΤΑΡΗΣ Σ. Ν.; ΤΣΑΠΑΚΗΣ Ε.; ΧΑΤΖΗΓΙΑΝΝΗ Ε. (Bulletin of the Geological Society of Greece, 2018)
The investigated area of Avlida (northern part of the South Evoikos Gulf), which obtained its present shape within Holocene, is characterised by shallow water depths (<12 m) and the presence of muddy sediments. The hydrological regime of the area is governed mainly by the tide (sea level fluctuation 0.25-0.4 m). The water column (in April 1998) found to be almost homogeneous with temperature and salinity to increase progressively with depth from 13.7 °C and 34.1 psu (surface) to 14.1 °C and 35.7 psu (near bed). Suspended sediment concentrations varied between 1 and 4 mg/1 with the highest values observed above the seabed (4-8 mg/I). These values of suspended sediment are relatively high when compared with other coastal areas, as that of Thermaikos Gulf (<1 mg/1). Furthermore, their presence is attributed primarily to the action of tidal currents assisted periodically by the wave activity and human interference i.e. navigation. Especially the high near bed values are associated with the near-bed activity of the tidal currents, which having usually velocities > 11 cm/s apply to the seafloor bottom shear velocities capable of causing resuspension of the surficial muddy sediments and inhibiting final deposition of the suspensates. Therefore, the fine-grained sediments are resuspended and subsequently advected by the tidal currents and eventually distributed all over the study area. Finally, the relatively coarse-grained sediments found to be more abundant at the southern part are related to the deltaic progradation within historical times of the torrential rivers Mégalo Rema and Lilantas which form the south-end part of the strait of Avlida.